Increasing the Competitiveness of Global MSMEs Amid Inflation Rate 2024-2025: Government Policy of the Government of Indonesia - Arisinta, Octaviana; Sakti, Norida Canda; Subroto, Waspodo Tjipto (Formosa Journal of Science and Technology, 2024)
Rising global inflation in 2024-2025 poses significant challenges for Micro, Small, and Medium Enterprises (MSMEs) in Indonesia. This study uses a qualitative method with literature analysis to explore government policies in increasing the competitiveness of MSMEs in the global market. The results of the study show that a comprehensive government strategy has had a positive impact on MSMEs in entering the international market. Cooperation between the government, MSME actors, and other stakeholders is urgently needed to create an ecosystem that supports the growth of MSMEs. The government needs to increase access to financing by providing credit programs that are affordable and easily accessible to MSMEs. In addition, support for the adoption of digital technologies, such as e-commerce and digital marketing, is crucial in expanding market reach. Training and skill development programs for MSME employees are also needed to improve the quality of human resources. Coordination between institutions must be improved to minimize inflation risks, as well as increase the transparency of inflation data to provide accurate information to the public. Sustainable and targeted policy implementation will maintain economic stability and encourage MSMEs to compete globally. Thus, the right government policies can strengthen the position of Indonesian MSMEs in the international market despite rising inflation.